Factors affecting the adoption of smart root washing innovation by commercial vegetable growers in the eastern suburbs of Bangkok, Thailand - Sornphakdee, N; Suwanmaneepong, S.; Llones, C. (International Journal of Agricultural Technology, 2025)
Result showed that 70% of the participa. nts were male, and the majority cultivated leafy vegetables. Natural canals emerged as the primary water source, with manual labour being the dominant washing method. All farmers washed vegetables manually, and 73.3% reported inadequate cleaning as their main post-harvest challenge. The adoption of the smart root washer received a moderate perceived utility score of 3.44, mirroring ratings for ease of use/complexity (mean=3.45). There was a consistent moderate perception across other adoption parameters, including observability (mean=3.44) and risk (mean=3.45). The technology’s adoption trajectory encompassed knowledge, persuasion, decision-making, implementation, and confirmation stages, registering moderate acceptance levels, with scores ranging between 3.28 and 3.45. Gender was the strongest predictor across all models, with the persuasion model having the highest absolute Beta coefficient (β=0.673). The consistent significance of gender differences suggested to play a crucial role in the adoption process.